Pelatihan Pembuatan RPS Berstandar Kerangka Kualifikasi Nasional Indonesia (KKNI) di Era Revolusi Industri 4.0 - Syafrizal Syafrizal; Ahmad Ahmad (STAI Auliaurrasyidin Tembilahan, 2021)
This training aims to improve lecturers competence in constructing RPS and assisting lecturers in compiling the document of RPS. This training was conducted at Islamic University of Indragiri (UNISI) involving 8 lecturers of English Department. This training and mentoring activity was divided into three sessions, first is conveying basic concept of RPS, second is constructing RPS and the third is discussing and presenting RPS. From a series of activities, it can be concluded that the ability of the English department lecturers of Islamic University of Indragiri has increased. This training is also able to correct errors made the lecturer in constructing RPS.